Structures last longer than intentions: creation of Ongomiizwin – Indigenous Institute of Health and Healing at the University of Manitoba. Issue 2 (28th January 2019) - Cook, Catherine; MacKinnon, Melanie; Anderson, Marcia; Whetter, Ian
ABSTRACT: Ongomiizwin – Indigenous Institute of Health and Healing at the University of Manitoba's Rady Faculty of Health Sciences (RFHS) was launched in June of 2017 with a mandate to provide leadership and advance excellence in research, education and health services to achieve health and wellness for Indigenous peoples and to implement the Truth and Reconciliation Commission of Canada's Calls to Action within the Faculty. The RFHS Reconciliation Action Plan has five broad themes: (1) Honoring traditional knowledge systems and practices, (2) Safe learning environments and professionalism, (3) Student support, mentorship and retention (4) Education across the spectrum and 5) Closing the gap in admissions. Community engagement is the focus of our work. Learners and practicing clinicians are grounded in the knowledge of ongoing colonial harms, engaged in critical self-reflection on one's own biases and trained to confront anti-indigenous racism in health care. This alignment is changing the health human resource landscape in northern Manitoba and beyond.